On the logical properties of Keynes's theorising, and different approaches to the Keynes–institutionalism nexus. Issue 4 (27th March 2019) - O'Donnell, Rod
Abstract: This paper replies to Hodgson (2019), which responds to my analysis and critique in O'Donnell (2018). My present aim is clarification of our respective positions, our agreements and disagreements, and their underlying causes. To this end, I elaborate further on the logic underpinning my initial paper, comment on several (not all) key points in Hodgson's response, and conclude with the matter of our different agendas. Space limitations preclude fuller discussion and encourage concise expression.